2014
DOI: 10.1007/s00436-014-4094-3
|View full text |Cite
|
Sign up to set email alerts
|

Besnoitia besnoiti tachyzoites induce monocyte extracellular trap formation

Abstract: Extracellular trap (ET) formation has been demonstrated as an important novel effector mechanism of polymorphonuclear neutrophils (PMN), eosinophils, mast cells and macrophages acting extracellularly against pathogens. In the present study, we show that tachyzoites of the emerging apicomplexan parasite Besnoitia besnoiti, that have recently been reported as potent inducers of PMN-derived ETosis, also trigger the release of ETs in an additional cell type, namely in monocytes. Fluorescence illustrations as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 46 publications
6
68
0
1
Order By: Relevance
“…Yousefi et al [9] described DNA release from eosinophils within 5 min of stimulation with complement component C5a or lipopolysaccharide (LPS), and the maximum effect, measured as fluorescence of a cell-impermeable DNA-staining dye, occurred within 30 min. METosis has been described as a rapid process that can occur in <30 min [22,23].…”
Section: Defining and Identifying Metsmentioning
confidence: 99%
See 4 more Smart Citations
“…Yousefi et al [9] described DNA release from eosinophils within 5 min of stimulation with complement component C5a or lipopolysaccharide (LPS), and the maximum effect, measured as fluorescence of a cell-impermeable DNA-staining dye, occurred within 30 min. METosis has been described as a rapid process that can occur in <30 min [22,23].…”
Section: Defining and Identifying Metsmentioning
confidence: 99%
“…Pretreatment with the actin cytoskeletal inhibitor, cytochalasin D, often used to block phagocytosis, has demonstrated the ability to decrease MET formation in some studies [25,26]. Cytochalasin D treatment did not have a significant effect on METosis of bovine monocytes exposed to B. besnoiti or murine J774A.1 macrophage-like cells in response to E. coli or C. albicans [23,28]. Aulik et al [25] reported that cytochalasin D reduced the bovine peripheral-blood and alveolar macrophage METosis response to M. haemolytica and its leukotoxin, but, in this same study, cytochalasin D had no significant effect on MET release from THP-1 or RAW 264.7 macrophagelike cells in response to E. coli hemolysin.…”
Section: Cellular Pathways Implicated In Met Releasementioning
confidence: 99%
See 3 more Smart Citations